“La guerra sucia no tiene cabida en nuestra política.” Un análisis del sistema de creencias (2005)
There is a relationship between social cognition and the conversational structures of discourse; theanalysis of beliefs systems, -upon getting to the bottom of those structure used to formulate explanationsover their functions and cognitive, social, political, historical, and cultural contexts; does not only encirclethe study of the discursive expression, but also the reproduction of ideology to which this latter belongsand represents. Furthermore, the conversational structures used in any discourse are influenced by theindividual social practices and reflect the mental model of he who carries it out.Based on these elements, an analysis over the beliefs system was carried out parting from the articlesthat were published around Colom bian President’s, Álvaro Uribe Vélez›s, speech before the UnitedNations’ General assembly in New York, on September, 29th, 2004. The analysis attempts to comparethe factual as well as the evaluative beliefs systems that are present in those articles published byvarious newspaper to outline that speech. Seven articles constitute the sample, including the speechtranscription. After the reading, some primary conclusions are presented in regards to the manipulationof factual beliefs (knowledge) in order to generate evaluative beliefs (opinions);b). the function of implicitexhortatory speech acts; and the relationship between the newspaper’s ideology and that of the journalists.